(3TQM efM GdhgGH aj QO GdacQ Edi GdUhGHs - (3eLghds ((3MaV Hf YHO Gddg Hf GdCejf Hf CMeO s)
(3ChdgG (B:s
(3CeG HYO , agPG TQM ehLR dHjGf GdeHge ef QLR hEfeG jWdH GdYde HGdfXQ , hdjS GdfXQ HeUjHI CHOkG , hdG eNWF CHOkG GdfXQ GdeUjH gh GdfXQ GdUMjM , ai GdfXQ GdMUMj ? JQJjH eYdhejf aUGYOkG Ydi LgI jJhUd HgG Zdi GdeWdhH s
(3BNQgG (B:s
(3bhdg (B: (3hEf jcf efaUdkG ZTGQI Zdi GdVQH GdKGfi , hgh GdGSJKfGA GdefaUd , hfYfi HGdefaUd GdePchQ (B: (3eG cGf MbjbjkG GfJgi s
(3GdfSNI HgG MhGTs
(3fSNI JGeIs
(3cJHJ HYV YHGQGJgG HGdMeQI s
(3hHgG LOGhd dHYV GdbVGjG GdefWbjI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3GdadSaI hGdefWbs